Limonene oxyfunctionalization over Cu-modified silicates employing hydrogen peroxide and t-Butyl hydroperoxide: Reaction pathway analysis - Vaschetti, Virginia María (2018)
Limonene oxidation over Cu-nanostructured mesoporous materials was studied. Three solids with different copper content were synthesized employing the template-ion exchange method, and physically-chemically analyzed by a multi-technical characterization. The performance of the molecular sieves as catalysts in the liquid phase oxyfunctionalization of limonene, employing hydrogen peroxide (H2O2) or t-butyl hydroperoxide (TBHP) as oxidants was evaluated. All synthesized Cu-MCM materials were active in the reaction. The obtained results showed that the used oxidant had an important influence on the products distribution under the employed conditions. With H2O2, compounds of high added value such as limonene oxide, carveol and carvone were mainly obtained. Meanwhile, with TBHP, limonene hydroperoxide turned out to be the major product. Finally, a reaction mechanism was proposed for each oxidant.